2014
DOI: 10.12983/ijsres-2014-p0340-0345
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Insecticides against Insect Pests and Predators Complex on Brassica napus L., Under Field Conditions

Abstract: Abstract. The present study was conducted in the research area of Cotton Research Station, Multan during spring 2011. The main objective of the study was to evaluate the effect of different insecticides against mustard aphid (Lipaphis erysimi Kalt.), leaf miner (Phytomyza horticola Gour.), seven spotted lady beetle (Coccinella septumpunctata L.) and syrphid fly larvae under field conditions. Bifenthrin, diafentheuron, dimethoate and imidacloprid were the insecticides used and data was recorded before 1 day and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Streibert et al (1988) reported that Diafenthiuron has a relatively low toxicity to beneficial insects. But Amin et al (2014) reported that Diafenthuron was highly toxic to C. septumpunctata as it showed maximum percent reduction (78.93%) after seven days of spray application. Ahn et al (2013) reported that Lufenuron did not show any toxic effect to honeybee and thought to be safe.…”
mentioning
confidence: 99%
“…Streibert et al (1988) reported that Diafenthiuron has a relatively low toxicity to beneficial insects. But Amin et al (2014) reported that Diafenthuron was highly toxic to C. septumpunctata as it showed maximum percent reduction (78.93%) after seven days of spray application. Ahn et al (2013) reported that Lufenuron did not show any toxic effect to honeybee and thought to be safe.…”
mentioning
confidence: 99%
“…The insect-toxin protein bioassay data were analyzed in one way ANOVA through "Statistix 8.1" and means were separated by Tukey-LSD test with significance level of 0.05 [27]. Standard errors of each concentration were also computed through Microsoft Excel 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Bana et al (2014) recorded the minimum population (2.67 and 2.10/10 plants)was recorded in imidacloprid. Amin et al (2014) found that Imidacloprid showed 57.34% reduction in C. septumpunctata population whereas dimethoate 52.77% reduction in larval population of syrphid flies after seven days of spray application. It is concluded that bifenthrin and imidacloprid can be used for the management of mustard insect pests because of their higher efficacy against aphids and leaf miners and less toxicity to beneficial insects.…”
Section: Effect Of Different Synthetic Insecticides and Biopesticidesmentioning
confidence: 91%